Peran Social Capital dan Literasi Digital dalam Meningkatkan Literasi Keuangan Syariah Generasi Z di Era Digital - Annisa Kusumawati; Arief Nurrahman; R. Andro Zylio Nugraha; Caesar Rosyad Achmadi; Agatha Saputri; Muhammad Harfiansyah Makarim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the digital era, the ability to utilize social networks and digital platforms to gain financial education and make financial decisions in accordance with sharia principles is increasingly essential. This study aims to analyze the influence of social capital and digital literacy on Islamic financial literacy among Generation Z. A quantitative approach was employed, with primary data collected from 209 respondents through purposive sampling, consisting of Generation Z individuals residing in Yogyakarta. Data analysis was conducted using path analysis with the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS), utilizing the SmartPLS 3.0 software. Construct reliability testing, discriminant validity, and hypothesis testing were carried out to evaluate the relationships between variables. The results indicate that social capital and digital literacy have a positive and significant effect on Islamic financial literacy. Digital literacy enhances individuals’ access to Islamic financial information through digital media, while social capital strengthens knowledge sharing and trust within communities. These findings highlight the importance of leveraging digital technology and reinforcing community-based approaches to improve Islamic financial literacy. This study contributes to the growing body of literature on the interaction between social capital, digital literacy, and Islamic financial literacy in the digital age and offers strategic insights for educational institutions and financial service providers to promote sharia-based financial literacy.